Child Protective Service Referrals Involving Exposure to Domestic Violence: Prevalence, Associated Maltreatment Types, and Likelihood of Formal Case Openings. (August 2019) - Victor, Bryan G.; Henry, Colleen; Gilbert, Terri Ticknor; Ryan, Joseph P.; Perron, Brian E.
Childhood exposure to domestic violence (CEDV) is widely understood as potentially harmful to children. Accordingly, many child welfare systems in the United States construe CEDV as maltreatment when the exposure results in harm or threatened harm to the child. The purpose of the current study was to investigate substantiated child welfare referrals directly related to CEDV to better understand the prevalence and patterns of CEDV-related maltreatment and how child welfare workers respond under the "harm or threatened harm" standard. Data were drawn from 23, 704 substantiated referrals between 2009 and 2013 in a large Midwestern child welfare system. Approximately 20% of substantiated referrals were CEDV related. A plurality of CEDV-related referrals included both a male caregiver and female caregiver who were co-substantiated for maltreatment. The most common maltreatment types substantiated for these referrals were neglect based rather than abuse based, and just under a quarter (23%) of CEDV-related referrals were formally opened for services. Referrals involving co-occurring substance abuse were most likely to be opened for services based on predicted probabilities derived from multilevel modeling. Implications for policy and practice are considered.